Réponses

  • Utilisateur Brainly
2014-09-12T06:12:47+02:00
A=(+5,6)+(-2,4)
A= 5,6 - 2,4
A= 3,2

B=(-9,1)+(-2,9)
B= - 9,1 - 2,9
B= - 12
C=(4,6)+(-3,7)
C= 4,6 - 3,7
C= 0,9

D=(+3,7)-(+8,6)
D= 3,7 - 8,6
D= - 4,9

E=(-1,5)-(-3,6)
E= 3,6 - 1,5
E= 2,1

F=(-5,4)-(+2,6)
F= - 5,4 - 2,6
F= - 8

2014-09-12T06:59:45+02:00
A = (+ 5,6) + (- 2,4)
A = 3,2

B = (- 9,1) + (- 2,9)
B = - 12

C = (4,6) + (- 3,7)
C = 0,9
D = (+ 3,7) - (+ 8,6)
D = 3,7 - 8,6
D = - 4,9

E = (- 1,5) - (- 3,6)
E = - 1,5 + 3,6
E = + 2,1

F = (- 5,4) - (+ 2,6)
F = - 5,4 - 2,6
F = - 8